ARTISTIC STYLE AND ITS FEATURES IN MODERN UZBEK POETRY - Berdiyeva Zebo Uralovna (Web of Journals Publishing, 2024)
In modern poetry, the article clearly reflects the creative person's attitude and assessment of the reality of life of his choice, the value of a particular work as an original work of art, ideological and aesthetic updates associated with the teaching principles of a particular folk poem. In the speech of heroes in the artistic style, simple speech words, sheva, vulgarisms are also used. In poetry, the position of artistic styles has increased to such an extent that the realization of their extortion of meaning, the correct understanding of the nature of complex metaphorical images, the role they play in it has been studied as a problem.